The Domination of “Street Art Culture” in the Interior Design of Cafés in the City of Malang - Eka Rahmawati, F; Anggrian, M (KnE Social Sciences, 2019)
The street art culture continues to flourish after the Reformation in Indonesia. Its development has not only been in the public space, but also in the field of interior design in certain segments. The high rate of consumerism has triggered a shift in the artistic function of street art, from street decoration to becoming part of the interior design of a café. The method of qualitative research with data collection techniques of interviews and direct observation was used in this research. Data was validated using data triangulation. Research results show that the development of street art used as a part of interior design in principle plays the role of communicating messages to the public. These messages serve as a way of conveying social issues and personal expressions of the artist. Murals in interior design communicate messages of aesthetics, sponsor, commerce, illustrations, and a “new lifestyle” that supports the concept of themes in a space. Street art murals that are used as a part of interior design have experienced a conceptual shift, but in regard to technique and motif are still the same as street art in general. The types of street art murals used in public spaces do not use only one mural motif; instead, they use a combination of several styles. Trends of street art murals di Malang include hand lettering, illustration, and character murals. Keywords: street art mural domination, café interior, Malang